Antimicrobial and Antioxidant Potential of Selected Seaweeds from Kodinar, Southern Coast of Saurashtra, Gujarat, India - Kannan Karthikeyan, Kewlani Shweta & , Ganapathi Jayanthi, Kolanthasamy Prabhu, Ganapathy Thirumaran (Journal of Applied Pharmaceutical Science, 2015)
The antimicrobial and antioxidant activity was evaluated for the marine seaweeds viz., Enteromorpha sp. Cystoseria indica, Sargassum swartzii, Gracilaria corticata, Caulerpa taxifolia and Caulerpa racemosa from Kodinar coast, Gujarat. Different solvents viz., methanol, ethanol, chloroform and diethyl ether were used for seaweed extraction to envisage the antibacterial activity against both Gram positive and Gram negative bacteria viz., Escherichia coli, Proteus sp., Pseudomonas aeruginosa, Klebsiella pneumoniae, and Staphylococcus aureus. Hydrogen peroxide scavenging assay and total antioxidant capacity were determined in ethanol extracted seaweeds. The maximum antibacterial activity was observed in the ethanol extract of all the seaweeds except C. racemosa. Among the seaweeds, the total antioxidant potential was found to be maximum in the ethanol extract of S. swartzii - 19.84±0.14 (19.8 mg of Ascorbic acid/g of seaweed extract) and the greatest H2O2 scavenging activity was shown by the ethanol extract of S. swartzii (81.63±0.39 % inhibition) compared to the control (ascorbic acid) 95.24±0.22. Hence, from the present study it is evident that the seaweeds collected from Kodinar coast harbors excellent inhibitory activity against various human pathogens and has significant antioxidant potential as well. In particular, the antimicrobial and antioxidant activity of S. swartzii was found to be excellent and can be pointed out as the best candidate among the other seaweeds tested.
Keywords: Seaweeds, Disc diffusion assay, Total antioxidant, H2O2 scavenging assay.